2008
DOI: 10.2174/092986708783330700
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Cytosine DNA Methyltransferase Dnmt1: Enzymatic Mechanism, Novel Mechanism-Based Inhibitors, and RNA-directed DNA Methylation

Abstract: This is a review of the enzymatic mechanism of DNA methyltransferase Dnmt1 and analysis of its implications on regulation of DNA methylation in mammalian cells and design of novel mechanism-based inhibitors. The methylation reaction by Dnmt1 has different phases that depend on DNA substrate and allosteric regulation. Consequently, depending on the phase, the differences in catalytic rates between unmethylated and pre-methylated DNA can vary between 30-40 fold, 3-6 fold or only 1 fold. The allosteric site and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 107 publications
(352 reference statements)
0
25
2
2
Order By: Relevance
“…Similar enzyme-based approach in studies of DNA methyltransferase lead to description of different regulation mechanisms almost 10 years before the initial ideas become the mainstream (Svedruzic, 2008;Svedruzic andReich, 2005a,2005b;Di Ruscio et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similar enzyme-based approach in studies of DNA methyltransferase lead to description of different regulation mechanisms almost 10 years before the initial ideas become the mainstream (Svedruzic, 2008;Svedruzic andReich, 2005a,2005b;Di Ruscio et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The mutations derived from the cytosine deamination might not be lethal for a bacterial cell and could help to prevent hydrolysis of cellular DNA by phage endonucleases. So, the ability of a C5-DNA MTase to catalyze deamination can turn out a physiological advantage for a bacterial cell [5]. On the contrary, mammalian cells are not likely to benefit from this kind of mutagenesis and therefore have developed mechanisms which provide low mutagenesis rate.…”
Section: Deamination Of Cytosine and 5-methylcytosinementioning
confidence: 99%
“…To date, the structural characteristics of the catalytic domain from different MTases, the details of the catalytic mechanism and the biological functions of C5-DNA MTases from different organisms are summarized in a variety of reviews (for example, see [1,[4][5][6][7][8]). Therefore, these aspects are discussed here rather briefly.…”
Section: Introductionmentioning
confidence: 99%
“…Dnmt1 is the principal DNA methyltransferase in mammalian cells [6, 12]. More than 20 different inhibitors of mammalian Dnmt1 have been described in the last 30 years [13].…”
Section: Introductionmentioning
confidence: 99%
“…The cytosine derivatives have been very useful in mechanistic studies of DNA methyltransferases [1820], however their full applicability as inhibitors of DNA methylation is very limited due to high toxicity in cells [13]. Very little improvement has been introduced following the initial studies, mostly due to the unusually challenging mechanism of the target base attack in the process of DNA methylation [12, 1822]. Consistent with earlier activity studies recent crystal structures showed that the target base attack depends on multiple flexible loops in the protein structure [1821, 23].…”
Section: Introductionmentioning
confidence: 99%